Women shop workers, 1918 (1918)
1918 1918-1939 "Women shop workers, 1918" [EP0054a], 1918 This letter from the National Amalgamated Union of Shop Assistants, Warehousemen and Clerks to Margaret Postgate [later Cole ] at the Fabian Research Department, dated 9 January, 1918, reports on the position of women shop and warehouse workers as regards equal pay, war bonuses and the minimum wage. The letter is from the Labour Research Department Archive.